PEMANFAATAN KONSELING KESEHATAN REPRODUKSI PADA PKPR WILAYAH KERJA PUSKESMAS BULU LOR - Tifani Novitriasti; Aditya Kusumawati; Syamsulhuda Budi Musthofa (Jurnal Kesehatan Masyarakat (Undip), 2020)
The Government of Indonesia has developed a program that aims to meet the needs of health services for adolescents namely Youth Care Health Services (PKPR). Bulu Lor health center is one of the PKPR health centers in the city of Semarang, but the scope of youth visits is still low, the number of reproductive health cases is still high and reproductive health counseling is still low. The purpose of this study was to analyze the use of reproductive health counseling at PKPR in the work area of Bulu Lor Public Health Center in Semarang. This research uses quantitative methods with cross sectional design. Respondents in this study were adolescents aged 10-19 years in the working area of Bulu Lor health center, amounting to 95 people. Sampling using multistage random sampling. Data collection uses interviews. Univariate data processing. The results showed that the behavior of the use of reproductive health counseling in PKPR in the work area of Bulu Lor puskesmas was still very low (8.4%). Most adolescents who have never done reproductive health counseling want to do reproductive health counseling (85.1%). The use of reproductive health counseling which is still very low is likely due to the uneven distribution of information related to PKPR and its services. Adolescent perceptions about reproductive health counseling should spend more time can encourage adolescents not to do reproductive health counseling. Therefore, the Bulu Lor health center needs to conduct socialization and education about PKPR, PKPR services and reproductive health to all adolescents in the Bulu Lor puskesmas work area by collaborating with schools and youth organizations and setting up counseling schedules outside school hours.